2020
DOI: 10.1159/000507281
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis Secondary to PD-1 and IDO Inhibition in a Patient with Refractory Glioblastoma

Abstract: Immune checkpoint inhibition (ICI)-based approaches have transformed the treatment landscape of numerous solid tumors. Glioblastoma (GBM) is an aggressive and almost universally fatal disease which is in need of novel treatment options, and combinations of immune checkpoint inhibitors, including dual agent therapy, are starting to be explored in refractory GBM. Growing adoption of ICI-based approaches in solid tumors has been met with improved understanding of immune-related adverse events (IRAEs), including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Even though the onset of HLH may occur at any time under ICI treatment, it appears that early onset of HLH is more likely. Most importantly, however, fatal outcome was reported in 16.2% of ICI-induced HLH cases -a rate that seems to be smaller than the death rates (up to 50%) reported for patients with HLH associated with other causes [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Even though the onset of HLH may occur at any time under ICI treatment, it appears that early onset of HLH is more likely. Most importantly, however, fatal outcome was reported in 16.2% of ICI-induced HLH cases -a rate that seems to be smaller than the death rates (up to 50%) reported for patients with HLH associated with other causes [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 61%
“…Primary or hereditary HLH (e.g., A91V mutation in PRF1) must be differentiated from secondary HLH, which is predominantly caused by infections, malignancies, and autoimmune conditions, frequently in the context of underlying immunodeficiency or immunosuppression. HLH is usually characterized by recurrent high fever, splenomegaly, pancytopenia, hyperferritinemia, hypertriglyceridemia, hypofibrinogenemia, increased IL-2R, and hemophagocytosis on bone marrow assessment [1][2][3][4][5][6][7][8][9][10]. Here we report a patient with metastatic melanoma who developed HLH after initiation of anti-CTLA-4/PD-1 treatment and give a brief tabular overview on previously reported cases.…”
Section: Introductionmentioning
confidence: 97%
“…We reviewed 11 cases of ICI‐induced HLH, including our cases (Table 3). 4–11 The median interval from the last dose to HLH diagnosis was 24 days; therefore, the two patients discussed in our report were diagnosed in the late phase. Based on the time interval, cases in which HLH was diagnosed after a long interval showed a lower HScore than those diagnosed after a short interval (Figure 2).…”
Section: Discussionmentioning
confidence: 79%
“…Satzger et al also reported one patient (7%) treated with a combination of corticosteroids and mycophenolate motif and did well 15 . One patient in reported cases (8%) was not diagnosed on time nor received treatment resulting in death (irHLH was confirmed on autopsy) 16 . Thus far, there is no consensus on treatment for irHLH, but most patients (10/13, 77%) seem to respond well to corticosteroid monotherapy or combination therapy per HLH‐2004 protocol.…”
Section: Discussionmentioning
confidence: 93%
“…15 One patient in reported cases (8%) was not diagnosed on time nor received treatment resulting in death (irHLH was confirmed on autopsy). 16 Thus far, there is no consensus on treatment for irHLH, but most patients (10/13, 77%) seem to respond well to corticosteroid monotherapy or combination therapy per HLH-2004 protocol. All irHLH patients in the literature review who received treatment (12/13, 92%) resulted in resolution of HLH (Table 1), thus indicating an excellent prognosis with ICIs-related cases.…”
Section: Discussionmentioning
confidence: 99%